Major central nervous system complications after allogeneic stem cell transplantation: A large retrospective study on 888 consecutive adult patients. (27th September 2020) - Mannina, Daniele; Berneking, Laura; Both, Anna; Timm, Wiebke; Urbanowicz, Tatiana; Wolschke, Christine; Ayuketang Ayuk, Francis; Fischer, Nicole; Fiehler, Jens; Grzyska, Ulrich; Rösner, Sabine; Choe, Chi‐Un; et al.
Abstract: Objectives: Major complications affecting the central nervous system (CNS) present a challenge after allogeneic stem cell transplantation (allo‐SCT). Methods: Incidence, risk factors, and outcome were retrospectively analyzed in 888 patients in a monocentric study. Results: Cumulative incidence (CI) of major CNS complications at 1 year was 14.8% (95%CI 12.3%‐17.2%). Median follow‐up is 11 months. CNS complications were documented in 132 patients: in 36 cases, classified metabolic; 26, drug‐related neurotoxicity (14 attributed to cyclosporine A, 4 to antilymphocyte globulin); 11, cerebrovascular (ischemic n = 8, bleeding n = 3); 9, infections; 9, psychiatric; and 9, malignant. The cause of CNS symptoms remained unclear for 37 patients (28%). Multivariate analysis demonstrated an association of CNS complication with patient age ( P  < .001). The estimated OS of patients with any CNS complication was significantly lower than in patients without neurological complications ( P  < .001), and the CI of non‐relapse mortality (NRM) was higher for patients with CNS complication ( P  < .001). A significant negative impact on survival can only be demonstrated for metabolic CNS complications and CNS infections (NRM, P  < .0001 and P  = .0003, respectively), and relapse ( P  < .0001). Conclusion: CNS complications after allo‐SCT are frequent events with a major contribution to morbidity and mortality. In particular, the situations of unclear neurological complications need to be clarified by intensive research.